The Effects of Specific Gut Microbiota on Hyperuricemia — A Mendelian Randomization Analysis and Clinical Validation - Αikepa D; He Y; Chen W; Liang M; Du Y; Chen X; Du M; Zhu Y; Wang J; Sun Y (Diabetes, Metabolic Syndrome and Obesity, 2025)
Dilinuer &Agr;ikepa,1,* Yi He,2,* Wujin Chen,3,* Meiting Liang,4 Yongkun Du,5 Xiaoyu Chen,1 Manxi Du,1 Yuqiu Zhu,1 Jianping Wang,6 Yuping Sun1,7,8 1Department of Microbiology, Xinjiang Medical University, Urumqi, People’s Republic of China; 2Department of Cell Biology and Genetics, Xinjiang Second Medical College, Karamay, People’s Republic of China; 3Department of Morphological Center, Xinjiang Medical University, Urumqi, People’s Republic of China; 4Department of Pathology, Xinjiang Second Medical College, Karamay, People’s Republic of China; 5Department of Critical Care Medicine, China-Japan Union Hospital of Jilin University, Changchun, People’s Republic of China; 6Department of Cardiology, The Fourth Affiliated Hospital of Xinjiang Medical University, Urumqi, People’s Republic of China; 7Key Laboratory of Xinjiang Uygur Autonomous Region, Laboratory of Molecular Biology of Endemic Diseases, Urumqi, People’s Republic of China; 8State Key Laboratory of Pathogenesis, Prevention, and Treatment of High Incidence Diseases in Central Asia, Urumqi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yuping Sun, Department of Microbiology, Xinjiang Medical University, No. 567 Shangde North Road, Shuimogou District, Urumqi, Xinjiang, 830017, People’s Republic of China, Email sunyuping@xjmu.edu.cnBackground: Hyperuricemia (HUA) is a metabolic disorder caused by an imbalance between uric acid (UA) production and excretion. It is closely associated with various diseases, including gout and kidney disease. The intestines play a significant role in UA excretion, and emerging evidence suggests that gut microbiota modulate UA excretion and degradation. However, the specific functional microbial biomarkers and their roles in HUA remain underexplored.Methods: Based on this, we hypothesize that the Mendelian randomization (MR) analysis method can be used to identify and define microbial biomarkers associated with HUA. Accordingly, we conducted an MR study using gut microbiota data from 18,340 participants across 24 distinct cohorts, including 129 HUA patients and 352,232 controls, to investigate the causal relationship.Results: We found that the genus Ruminococcus was linked to a lower risk of HUA, while the family Clostridiaceae was associated with a higher risk of HUA. Clinical validation showed that high Clostridiaceae and low Ruminococcus abundance could distinguish HUA patients from healthy individuals, and the predictive diagnostic efficacy of Clostridiaceae was better. The combined model further enhanced diagnostic accuracy.Conclusion: Our findings provide important information on the micro-biome features of HUA and novel insights into the further determination of the roles of the involved microorganisms, providing a reference for disease diagnosis and the development of microbial therapies.Keywords: gut microbiome, hyperuricemia, Mendelian randomization, diagnostic model